A hydrophilic salt-carrying separator and a method of manufacturing the same, and a water-activated battery

CN122992279APending Publication Date: 2026-10-27CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610819381.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-08
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

放电过程中,负极表面会产生气体(例如氢气),若隔膜无法有效引导气体排出或促进气液交换,气泡将在电极表面积累,显著降低有效反应面积,导致局部电流密度升高、极化加剧,从而延缓电压建立,拖长激活时间

Benefits of technology

[0019]本发明具有的有益效果是:采用棉线作为隔膜线的基材,利用其丰富的微孔和毛细结构,使电解液能够快速驱替内部空气,为快速激活奠定基础。通过亲水处理降低纤维界面张力,使电解液更快速浸润隔膜线;通过载盐处理使隔膜线自身携带电解质盐,注液后形成更高离子电导率的局部电解液环境,既可提升常规电解液的电导率表现,又能赋予电池淡水激活能力。上述处理的协同作用,使隔膜线的吸液速度、浸润能力及电导率特性得到提升,从而显著缩短水激活电池的激活时间。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a hydrophilic salt-loaded diaphragm thread and a preparation method thereof and a water-activated battery, and the preparation method of the hydrophilic salt-loaded diaphragm thread comprises the following steps: immersing a cotton thread base material in a first solution to perform hydrophilic treatment, so as to obtain a hydrophilic cotton thread; immersing the hydrophilic cotton thread in a second solution to perform salt loading treatment, so as to obtain a hydrophilic salt-loaded diaphragm thread; wherein the first solution contains a first surfactant, and the second solution contains an electrolyte salt. The cotton thread is used as the base material, the abundant micropores and capillary structures of the cotton thread lay a foundation for fast activation of the battery; through the hydrophilic treatment and the salt loading treatment, the liquid absorption speed, the wetting capacity and the conductivity characteristics of the diaphragm thread are synergistically improved, and the activation time of the water-activated battery is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water-activated battery technology, and in particular to a hydrophilic salt-loaded separator line and its preparation method, and a water-activated battery. Background Technology

[0002] Water-activated batteries, as a type of reserve battery, can be stored for a long time in a dry state. When needed, they can be quickly activated and powered by injecting water or an aqueous electrolyte. They have significant advantages such as fast activation speed, long storage life, and good environmental adaptability, and have important application value in military equipment, emergency power supplies, and underwater equipment.

[0003] In water-activated batteries (taking the magnesium / silver chloride system as an example), the cell typically employs a wound structure, consisting of a positive electrode, a negative electrode, and a separator. The core functions of the separator include isolating the positive and negative electrodes to prevent internal short circuits, ensuring rapid wetting and efficient transport of the electrolyte, and ensuring the smooth discharge of gaseous products. For water-activated batteries requiring fresh water activation, the separator also needs to have the ability to carry the electrolyte to support electrochemical reactions. During discharge, gas (such as hydrogen) is generated on the surface of the negative electrode. If the separator cannot effectively guide the gas out or promote gas-liquid exchange, bubbles will accumulate on the electrode surface, significantly reducing the effective reaction area, leading to increased local current density and intensified polarization, thereby delaying voltage build-up and prolonging the activation time.

[0004] Currently, the separators widely used in water-activated batteries (such as PER separators) mainly suffer from the following problems: First, insufficient hydrophilicity makes it difficult to quickly displace the air inside the cell after electrolyte injection, resulting in delayed separator wetting and the inability to establish the electrochemical reaction immediately; second, obstructed gas-liquid exchange channels make it difficult for gaseous products to be quickly discharged, exacerbating the accumulation of bubbles on the electrode surface. These problems collectively lead to an activation time for water-activated batteries that generally exceeds 2 seconds, making it difficult to meet increasingly stringent application requirements. Summary of the Invention

[0005] The purpose of this invention is to provide a hydrophilic salt-carrying membrane line and its preparation method, as well as a water-activated battery, to solve the problems in the prior art.

[0006] The technical solution adopted in this invention includes: a method for preparing a hydrophilic salt-carrying membrane line, comprising the following steps:

[0007] The cotton thread substrate is immersed in the first solution and subjected to hydrophilic treatment to obtain hydrophilic cotton thread;

[0008] The hydrophilic cotton thread is immersed in the second solution and subjected to salt loading treatment to obtain a hydrophilic salt-loaded diaphragm thread.

[0009] The first solution contains a first surfactant, and the second solution contains an electrolyte salt.

[0010] Preferably, the second solution contains a second surfactant, and the first surfactant and the second surfactant are each independently selected from one or both of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate.

[0011] Preferably, the concentration of sodium dodecylbenzenesulfonate in the first solution is 0.5 mmol / L to 5 mmol / L, and the concentration in the second solution is 0 mmol / L to 5 mmol / L.

[0012] Preferably, the concentration of sodium dodecyl sulfate in the first solution is 5 mmol / L to 15 mmol / L, and the concentration in the second solution is 0 mmol / L to 15 mmol / L.

[0013] Preferably, the electrolyte salt includes at least one of potassium salt and sodium salt, and the concentration of the electrolyte salt in the second solution is 0.5 mol / L to 5 mol / L.

[0014] Preferably, the solvent for the first solution and the solvent for the second solution are water.

[0015] Preferably, the cotton thread substrate is immersed in the first solution for a first time and then dried at a first temperature to obtain hydrophilic cotton thread; the first time is ≥10 min and the first temperature is 80~160℃.

[0016] Preferably, the hydrophilic cotton thread is immersed in the second solution for a second time and then dried at a second temperature to obtain a hydrophilic salt-loaded membrane thread; the second time is 1s to 30s and the second temperature is 80 to 160℃.

[0017] The technical solution of the present invention also includes: a hydrophilic salt-carrying membrane line, which is prepared by the above-mentioned method for preparing hydrophilic salt-carrying membrane lines.

[0018] The technical solution of the present invention also includes: a water-activated battery, wherein the above-mentioned hydrophilic salt-carrying membrane line is contained.

[0019] The beneficial effects of this invention are as follows: Using cotton thread as the substrate for the separator allows for rapid displacement of internal air by the electrolyte, leveraging its abundant micropores and capillary structure, thus laying the foundation for rapid activation. Hydrophilic treatment reduces the interfacial tension of the fibers, enabling the electrolyte to wet the separator thread more quickly. Salt loading treatment allows the separator thread to carry electrolyte salts, creating a localized electrolyte environment with higher ionic conductivity after electrolyte injection. This not only improves the conductivity of conventional electrolytes but also endows the battery with freshwater activation capability. The synergistic effect of these treatments enhances the separator thread's liquid absorption rate, wetting ability, and conductivity characteristics, thereby significantly shortening the activation time of water-activated batteries. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] A first aspect of this invention provides a method for preparing a hydrophilic salt-loaded membrane wire, comprising the following steps: immersing a cotton thread substrate in a first solution for hydrophilic treatment to obtain a hydrophilic cotton thread; then immersing the hydrophilic cotton thread in a second solution for salt loading treatment to obtain a hydrophilic salt-loaded membrane wire. The first solution contains a first surfactant, and the second solution contains an electrolyte salt.

[0022] Because cotton thread itself has abundant micropores and capillary structures, it has natural advantages in liquid absorption and air release. Therefore, this solution uses cotton thread as the substrate for the separator wire, allowing the electrolyte to quickly displace the air inside the separator wire after battery filling, thus laying the foundation for rapid activation. However, the physical structure of cotton thread alone is still insufficient to meet the increasingly stringent requirements for activation time. Therefore, this invention further performs hydrophilic treatment and salt loading treatment on the cotton thread substrate.

[0023] Hydrophilic treatment reduces interfacial tension by modifying the first surfactant, allowing the electrolyte to wet the separator wire more quickly. Salt loading treatment enables the separator wire to carry electrolyte salts. After electrolyte injection, the liquid dissolves the salts carried by the separator wire, creating an electrolyte environment with higher ionic conductivity near the separator wire. This not only improves the conductivity of conventional electrolytes but also enables the battery to be activated directly with fresh water. Through the synergistic effect of these two treatments, the separator wire's liquid absorption rate, wetting ability, and conductivity characteristics are further improved, thereby significantly shortening the activation time of water-activated batteries.

[0024] Furthermore, the process sequence of hydrophilic treatment followed by salt loading in this invention has significant synergistic effects. During the hydrophilic treatment stage, the first surfactant is loaded onto the cotton yarn substrate, effectively reducing the interfacial tension of the fibers. This allows the second solution in the subsequent salt loading process to penetrate more deeply into the internal pores and between fiber bundles, thereby improving the uniformity and amount of salt loading.

[0025] The first surfactant includes one or both of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate, and the electrolyte salt includes one or both of potassium salt and sodium salt. Since both of these substances have good water solubility and can dissolve completely without the aid of organic solvents or other special media, the solvents for the first and second solutions can be pure water or ultrapure water.

[0026] After each processing step, the material needs to be dried to remove residual solvent inside and on the surface of the fibers, preventing the solvent from adversely affecting subsequent processing steps or the performance of the final diaphragm line. Specifically, the hydrophilic cotton thread needs to be dried to remove water from the first solution, allowing the first surfactant to firmly adhere to the fiber surface before salt loading treatment. After salt loading treatment, it also needs to be dried to remove solvent from the second solution, allowing the electrolyte salt to be evenly loaded onto the fibers of the hydrophilic cotton thread, finally obtaining a dried hydrophilic salt-loaded diaphragm line.

[0027] Although drying allows the first surfactant to adhere more firmly to the cotton thread substrate, during the subsequent salt loading process, when the hydrophilic cotton thread is immersed in the second solution (aqueous solution), a small amount of the first surfactant inevitably redissolves and enters the solution, resulting in the loss of the hydrophilic modification layer of the cotton thread. This, in turn, affects the final hydrophilicity and liquid absorption rate of the diaphragm thread. To address this issue, this solution adds a second surfactant to the second solution. This second surfactant is independently selected from one or both of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate. By adding the second surfactant to the second solution, a secondary hydrophilic modification of the cotton thread can be performed during the salt loading process, effectively compensating for the dissolution loss of the first surfactant, thereby ensuring that the final diaphragm thread has good hydrophilicity.

[0028] In a preferred embodiment, the specific type and concentration of the first surfactant can be selected according to actual needs. When sodium dodecylbenzenesulfonate is used as the first surfactant, its concentration in the first solution is preferably 0.5 mmol / L to 5 mmol / L; when sodium dodecyl sulfate is used as the first surfactant, its concentration in the first solution is preferably 5 mmol / L to 15 mmol / L. The determination of the above concentration range takes into account the differences between the molecular structures of different surfactants and their hydrophilic modification efficiency, while also balancing economy and treatment effect.

[0029] Since the amount of the first surfactant lost due to dissolution during salt loading is relatively small, the amount of the second surfactant added to the second solution can be adjusted adaptively according to the type and amount of the first surfactant, without the need for excessive addition. Specifically, when sodium dodecylbenzenesulfonate is used as the second surfactant, the concentration of the second surfactant in the second solution is preferably 0 mmol / L to 5 mmol / L; when sodium dodecyl sulfate is used as the second surfactant, the concentration of the second surfactant in the second solution is preferably 0 mmol / L to 15 mmol / L. The above range covers various options from no addition at all (i.e., relying solely on the residual adhesion of the first surfactant) to appropriate supplementation, and can be flexibly selected according to process requirements and cost control in actual production.

[0030] It should be noted that a concentration limit of 0 mmol / L does not mean that the second surfactant is optional. Rather, it indicates that in some cases, if the first surfactant adheres firmly and the dissolution loss is minimal, the addition of the second surfactant can theoretically be omitted. However, in most preferred solutions, it is still recommended to add an appropriate amount of the second surfactant to the second solution to ensure the stability and consistency of the hydrophilic properties of the finished diaphragm line.

[0031] In a preferred embodiment, potassium chloride or sodium chloride is preferably used as the electrolyte salt. These two salts have advantages such as high solubility, wide availability, low cost, and no adverse effects on the electrochemical system. In specific implementation, the concentration of potassium chloride or sodium chloride in the second solution is preferably 0.5 mol / L to 5 mol / L. Within this concentration range, it is possible to ensure that the diaphragm line is loaded with a sufficient amount of electrolyte salt in subsequent processing, thereby forming a local electrolyte environment with high ionic conductivity after liquid injection. At the same time, it can avoid problems such as crystallization, excessively thick salt layer on the fiber surface, or difficulty in drying caused by excessive salt concentration, which is conducive to obtaining a diaphragm line product with uniform salt loading and stable performance.

[0032] The specific operations of this method include: fully immersing the cotton thread substrate in a first solution, maintaining this for a first time, removing it, draining it, and then transferring it to a first temperature for drying to obtain hydrophilic cotton thread. The first time should be no less than 10 minutes to ensure that the first surfactant has sufficient time to be uniformly loaded onto the cotton thread substrate; the first temperature is controlled between 80 and 160°C. This temperature range effectively removes moisture from the cotton thread substrate, allowing the first surfactant to adhere firmly, while avoiding excessively high temperatures that could cause thermal damage to the cotton fibers or decomposition and inactivation of the first surfactant.

[0033] The specific operation of this method also includes: fully immersing the hydrophilic cotton thread in the second solution, maintaining it for a second time, removing it, draining it, and then transferring it to a second temperature for drying to obtain a hydrophilic salt-loaded separator thread. The second time is preferably 1s to 30s to ensure the second solution fully wets the cotton thread fibers while avoiding excessive dissolution and loss of the first surfactant. The second temperature is controlled between 80 and 160℃ because the drying temperature significantly affects the crystallization process of the electrolyte salt: at lower temperatures, the required drying time is longer, and the salt crystals tend to grow too large, which slows down the dissolution rate after electrolyte injection, thus affecting the battery's activation performance; as the temperature increases, the required drying time is correspondingly shortened, and the crystals are less likely to grow excessively, forming appropriately sized fine crystals, which is beneficial for rapid dissolution after electrolyte injection; however, the temperature cannot be too high, otherwise it may cause thermal damage to the cotton thread fibers or decomposition and failure of the surfactant.

[0034] During implementation, the first and second drying times should not be less than 20 minutes each to ensure that the solvent inside and on the surface of the cotton fibers is fully removed, allowing the surfactants and electrolyte salts to be firmly loaded onto the fibers. If the drying time is too short, residual moisture may cause the surfactants or salts to migrate and distribute unevenly, thus affecting the stability and consistency of the final performance of the diaphragm line.

[0035] A second aspect of this invention provides a hydrophilic salt-loaded separator wire, which is prepared using the above-described method. The separator wire treated by this method exhibits excellent hydrophilic properties on its surface, with a suitable amount of electrolyte salt uniformly loaded inside and on the surface of the fibers, while retaining the original abundant pores and capillary structure of the cotton thread substrate. When applied to water-activated batteries, this hydrophilic salt-loaded separator wire enables rapid liquid absorption, smooth venting, rapid establishment of electrochemical reactions, and effectively shortens battery activation time, making it particularly suitable for applications with strict requirements for activation speed.

[0036] A third aspect of the present invention provides a water-activated battery containing the above-described hydrophilic salt-carrying membrane line.

[0037] The following are specific embodiments of the present invention.

[0038] Example 1

[0039] Sodium dodecylbenzenesulfonate was fully dissolved in pure water to prepare the first solution, wherein the concentration of sodium dodecylbenzenesulfonate was 1.2 mmol / L.

[0040] The cotton thread substrate was immersed in the first solution for 10 minutes to perform hydrophilic treatment. After completion, it was removed, drained, and transferred to an electric heating drying oven. It was dried at 110°C for 20 minutes to obtain hydrophilic cotton thread.

[0041] Potassium chloride was dissolved in pure water, and sodium dodecylbenzenesulfonate was added and dissolved completely to prepare a second solution, wherein the concentration of potassium chloride was 2 mol / L and the concentration of sodium dodecylbenzenesulfonate was 0.6 mmol / L.

[0042] The hydrophilic cotton thread was immersed in the second solution for 5 seconds to carry out salt loading treatment. After completion, it was taken out and drained, and then transferred to an electric heating drying oven and dried at 110℃ for 20 minutes to obtain the hydrophilic salt-loaded diaphragm thread.

[0043] Since there is no precedent for using cotton thread as a separator material in the field of water-activated batteries, there is a lack of standardized characterization methods specifically for the hydrophilic properties of such materials. Therefore, this embodiment refers to the method for determining sinking time and water absorption in the pharmaceutical industry standard YY / T0330-2015, and the method for determining wicking height in the textile industry standard FZ / T01071, to evaluate the hydrophilic properties of untreated cotton thread substrate, hydrophilic cotton thread obtained only through hydrophilic treatment, and hydrophilic salt-loaded separator thread obtained through both hydrophilic treatment and salt loading treatment. The test results are shown in Table 1.

[0044] The sinking time test method is as follows: Take a 1m long cotton thread, fold it in half 8 times, and release it freely from 10cm above the liquid surface to allow it to contact the water surface. Record the time required for the cotton thread to completely sink below the water surface after absorbing liquid. The shorter the sinking time, the better the hydrophilicity of the material. The water absorption test method is as follows: Measure the mass change of a unit mass of cotton thread before and after immersing it in pure water for 30 seconds, and calculate its weight gain percentage. The greater the water absorption, the better the hydrophilicity of the material. The wicking height test method is as follows: Measure the height of water rising vertically along the cotton thread through capillary action within 30 seconds. The greater the wicking height, the stronger the capillary liquid absorption capacity of the material.

[0045] Table 1

[0046]

[0047] Example 2

[0048] Untreated cotton thread substrate, the hydrophilic salt-loaded membrane thread prepared in Example 1, and a PER membrane were used to assemble water-activated batteries with a magnesium alloy negative electrode and a silver chloride positive electrode, respectively. The cotton thread substrate and the hydrophilic salt-loaded membrane thread were wound around the outside of the silver chloride positive electrode to isolate the magnesium alloy negative electrode; the PER membrane was cut and placed directly between the magnesium alloy negative electrode and the silver chloride positive electrode. Each battery group adopted a four-cell series-connected wound structure. Under the same test conditions, each battery group underwent electrolyte injection activation tests. The moment of injection of fresh water as electrolyte was taken as the activation time origin. The time taken for the voltage of each battery group to rise to the working voltage (i.e., not lower than 4.5V) was measured, and this time was the activation time. The working voltage of the battery was also recorded. The specific test results are shown in Table 2.

[0049] Table 2

[0050]

[0051] According to the data in Table 2, the battery assembled with the hydrophilic salt-loaded separator wire prepared in this embodiment not only has a shorter activation time but also a higher operating voltage. This is because the separator wire has excellent hydrophilicity, which can quickly displace the air inside the cell after liquid injection, effectively reducing the accumulation of air bubbles on the electrode surface, thereby increasing the effective reaction area and reducing local current density and polarization.

[0052] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the claims, or equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a hydrophilic salt-carrying membrane line, characterized in that, Including the following steps: The cotton thread substrate is immersed in the first solution and subjected to hydrophilic treatment to obtain hydrophilic cotton thread; The hydrophilic cotton thread is immersed in the second solution and subjected to salt loading treatment to obtain a hydrophilic salt-loaded diaphragm thread. The first solution contains a first surfactant, and the second solution contains an electrolyte salt.

2. The method for preparing the hydrophilic salt-carrying membrane line according to claim 1, characterized in that, The second solution contains a second surfactant, and the first surfactant and the second surfactant are each independently selected from one or both of sodium dodecylbenzenesulfonate and sodium dodecyl sulfate.

3. The method for preparing the hydrophilic salt-carrying membrane line according to claim 2, characterized in that, The concentration of sodium dodecylbenzenesulfonate in the first solution is 0.5 mmol / L to 5 mmol / L, and the concentration in the second solution is 0 mmol / L to 5 mmol / L.

4. The method for preparing the hydrophilic salt-carrying membrane line according to claim 2, characterized in that, The concentration of sodium dodecyl sulfate in the first solution is 5 mmol / L to 15 mmol / L, and the concentration in the second solution is 0 mmol / L to 15 mmol / L.

5. The method for preparing the hydrophilic salt-carrying membrane line according to claim 1, characterized in that, The electrolyte salt includes at least one of potassium and sodium salts, and the concentration of the electrolyte salt in the second solution is 0.5 mol / L to 5 mol / L.

6. The method for preparing the hydrophilic salt-carrying membrane line according to claim 1, characterized in that, The solvent for both the first and second solutions is water.

7. The method for preparing the hydrophilic salt-carrying membrane line according to claim 1, characterized in that, After immersing the cotton thread substrate in the first solution for a first time, it is transferred to a first temperature for drying to obtain hydrophilic cotton thread. The first duration is ≥10 minutes, and the first temperature is 80~160℃.

8. The method for preparing the hydrophilic salt-carrying membrane line according to claim 1, characterized in that, After immersing the hydrophilic cotton thread in the second solution for a second time, it is transferred to a second temperature and dried to obtain a hydrophilic salt-loaded membrane thread; the second time is 1s~30s, and the second temperature is 80~160℃.

9. A hydrophilic salt-carrying membrane line, characterized in that, The hydrophilic salt-carrying membrane line is prepared by the method described in any one of claims 1-8.

10. A water-activated battery, characterized in that, The water-activated battery contains the hydrophilic salt-carrying membrane line as described in claim 9.